UPAYA MENINGKATKAN HASIL BELAJAR PENDIDIKAN ALQURAN MATERI SURAH AL-FALAQ DAN SURAH AN-NASR DENGAN MENERAPKAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH PADA SISWA KELAS IV C SDN 3 SYAMSUDIN NOOR BANJARBARU - Nurjani Nurjani; Muhamad Ramli; Siti Rahmawati (Program Studi PAI STAI Al Falah Banjarbaru, 2018)
This study discusses the efforts to improve the learning outcomes of Quranic Education by applying the cooperative learning model type make a match. The purpose of this study was to find out through the application of cooperative learning models the type of make a match can improve learning outcomes of Quranic Education in fourth grade C SDN 3 Syamsudin Noor students and the process of applying cooperative learning model type make a match in Quranic Education subjects in grade IV C students SDN 3 Syamsudin Noor. The method in this study uses qualitative descriptive with the type of participant class action research. Subjects in this study were all students of grade IV C SDN 3 Syamsudin Noor. While the object in this study is an increase in learning outcomes and the process of applying cooperative learning model type make a match. Based on the results of the study, it is known that through the application of cooperative learning models the type of make a match can improve the learning outcomes of Quranic Education in grade IV C SDN 3 Syamsudin Noor students. This can be seen from the achievement of research success indicators namely qualitative indicators and quantitative indicators. Qualitative indicators are seen in terms of the process of student activity and teacher activity. The average value of student activity in the first cycle is 80.15 and in the second cycle is 92.96. While the average value of teacher activity in cycle I am 85 and in cycle II is 100. This shows that the activeness of students and teachers are very good criteria. Quantitative indicators are seen in terms of the results of the pre-cycle classical completeness which initially only 31.25% increased in the first cycle to 65.62% and in the second cycle increased again to 100%. The process of applying cooperative learning model type make a match in the Quranic Education subject to grade IV C SDN 3 Syamsudin Noor students runs effectively and efficiently in accordance with the steps that have been determined. This can be seen from the increased activity of students in following the learning process of Quranic Education. Keywords: Learning Outcomes, Qur'anic Education, Cooperative Learning Models, make a match.